2017
DOI: 10.1590/0074-02760160305
|View full text |Cite
|
Sign up to set email alerts
|

Scoring clinical signs can help diagnose canine visceral leishmaniasis in a highly endemic area in Brazil

Abstract: Canine visceral leishmaniasis (CVL) diagnosis is still a challenge in endemic areas with limited diagnostic resources. This study proposes a score with the potential to distinguish positive CVL cases from negative ones. We studied 265 dogs that tested positive for CVL on ELISA and parasitological tests. A score ranging between 0 and 19 was recorded on the basis of clinical signs. Dogs with CVL had an overall higher positivity of the majority of clinical signs than did dogs without CVL or with ehrlichiosis. Cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
2
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 30 publications
4
27
2
3
Order By: Relevance
“…This characteristic of the test may explain that most of the CVL-seropositive dogs found in the municipality of Iguatama are symptomatic. In symptomatic dogs, onychogryphosis, weight loss, and mucosa were more frequently observed, findings consistent with Silva et al (2017).…”
Section: Discussionsupporting
confidence: 60%
“…This characteristic of the test may explain that most of the CVL-seropositive dogs found in the municipality of Iguatama are symptomatic. In symptomatic dogs, onychogryphosis, weight loss, and mucosa were more frequently observed, findings consistent with Silva et al (2017).…”
Section: Discussionsupporting
confidence: 60%
“…studies, but generally these clinical signs are the most commonly reported in the literature. These results corroborate the findings of several authors [25,26]. Regarding gender, there was a greater predominance of males in infected dogs and females in dogs in the control group.…”
Section: Discussionsupporting
confidence: 92%
“…Once again, these findings represent the systemic nature of the disease (CIARAMELLA et al, 1997). Nevertheless, ocular findings are relevant for this disease in dogs and can aid in the diagnosis (SILVA et al, 2017). Normocytic normochromic anemia was the most prevalent hematological alteration, affecting 82.6% (60/73) dogs.…”
Section: Resultsmentioning
confidence: 95%